Investigating the relationship between homework and academic achievement in elementary students - Akram Hafezi; Samira Etemadinia (Goodwood Publishing, 2022)
Purpose: The purpose of this study was to investigate the relationship between homework and academic achievement in elementary students. Research methodology: The statistical population includes students in the fifth year of the elementary school in Tehran. Using the random sampling method, 160 people were selected as the research sample. The tool used to collect data is a researcher-made questionnaire. The statistical method used is the calculation of correlation coefficient and chi-square. Results: The results of the analysis showed that there is a significant relationship between homework and academic achievement. Limitations: One of the problems of the research was the lack of resources which was considered a serious problem and the other was in the implementation of the questionnaire. Contribution: This study is expected can give a piece of knowledge about the relationship between homework and students' academic achievement.